DETERMINING THE PREVALENCE AND SOCIO-DEMOGRAPHIC CORRELATES OF HIRSUTISM AMONG FEMALE RESIDENTS OF MUZAFFARABAD CITY, AJK (The Research of Medical Science Review, 2024)
Hirsutism is the presence of an excessive growth of the terminal hairs over the body surface of an individual usually among females in a male-like pattern. The primary objective of the study was to determine the prevalence of hirsutism among females of age group 15-49 years in the Muzaffarabad City, Azad Jammu and Kashmir, Pakistan. This was a descriptive cross-sectional study in which participants were selected randomly in the gynecological wards and beauty parlors of the Muzaffarabad region during the period from May to December 2016. The distribution of the body hair was recorded using modiﬁed Ferriman-Gallwey (mF-G) scoring system. The age of the participants ranged from 15-49 years. Mean age was 27.1 and standard deviation was 7.34 years. About 64.4 percent of the participants were married and 11.7 percent were obese. The common accompanying disorders were acne (36.4 percent), hypertrichosis (25.3 percent), family history of hirsutism (22.2 percent) and menstrual irregularity (68.5 percent). The prevalence of hirsutism among participants was 43.0 percent. The mean, median and mode of the total mF-G scores were 7.1, 7.0 and 5.0 respectively. The lower abdomen had the highest mean value of 1.38 while lower back had the lowest mean value of 0.25. All the nine variables had significant correlations with the total hirsutism scores however the lower abdomen score had the strongest correlation of 0.83. The 37.0 percent of the participants were from the mild category, 5.6 percent belonged to the moderate category and 0.6 percent belonged to the severe category of the hirsutism according to the mF-G scoring method.